APPLICATION OF OPTIMAL CONTROL THEORY TO INVENTORY PROBLEMS THAT ARE INCREASING AT PT. INDUSTRY PLYWOOD TJIPTA RIMBA DJAJA - Harahap, Tramilta Salsabila; Dur, Sajaratud; Husein, Ismail (Journal of Mathematics and Scientific Computing With Applications, 2022)
Every company that carries out businees activities generally has inventory. Inventories include raw materials, semi-finished goods or finished goods. Inventories of goods in the company have increased and decreased. An increase in inventory can cause losses, because the cost of storing and maintaining in the warehouse is too high. While a decrease in inventory can result in a shortage of inventory. The purpose of this research is to determine the level of optimal inventory in PT. Industry Plywood Tjipta Rimba Djaja. Using the optimal control theory model and analyzing the stability of the dynamic differential equation, to find the optimal inventory level. Obtained optimal inventory levels achieve stability at the time . For the planning length of 12 months includes: raw material inventory (logs sengon and rambung), production (finished materials in process) and finished plywood or plywood products that are in the warehouse. From this research optimal control theory can be applied in PT. Industry Plywood Tjipta Rimba Djaja to optimize inventory on the problem of increasing inventory.